Promotion and support of breastfeeding: which role for a hospital portal? - Giuseppe Giordano (Hygeia Press di Corridori Marinella, 2017)
The encouragement and the support of breastfeeding are public health priorities. Since 2013 "Ospedali Riuniti" of Palermo has been running a portal to promote initiation and duration of breastfeeding. The "Allattamenti Riuniti" portal provides women with information and individualized answers in case of breastfeeding problems. The activity of the service between April 2013 and January 2017 has been assessed. We illustrate the characteristics of mothers and the kind of questions asked.